A secure two-qubit quantum model for segmentation and classification of brain tumor using MRI images based on blockchain - Amin, Javaria; Anjum, Muhammad Almas; Gul, Nadia; Sharif, Muhammad (Neural computing & applications, 2022)
The size of the medical imaging data is increasing day by day which requires improved tools/applications to perform accurate and efficient diagnoses. Another important concern is to secure the patient's personal information. Therefore, this research work focuses on a novel secure framework for brain tumor diagnosis. The proposed methodology comprises three main core steps. Initially, the patient's MRI data are encrypted and decrypted using the SHA-256 algorithm to secure the brain data. The decrypted images are supplied to the 2-qubit quantum model named Javeria (J). Quantum model for tumor classification, which comprises three layers as two dense layers and one Keras layer with a softmax activation unit. The classified tumor images are input to the semantic segmentation model named J. SegCNN for tumor segmentation. The proposed J. SegCNN model contains 11 layers that are trained on selected batch-size and Adam optimizer solver. The proposed model provides a 98% dice similarity coefficient (DSC) which is far better as compared to the latest research works.